Peningkatan Kemampuan Komunikasi Matematis Siswa SMA Melalui Model Problem-based Learning Berbantuan Quizizz - Larisa, Erinna; Fisher, Dahlia; Saputra, Jusep (Papanda, 2026)
Mathematical communication skills are one of the important competencies in mathematics learning; however, many students still experience difficulties in expressing ideas and solutions systematically. This study aims to analyze the improvement of high school students’ mathematical communication skills through the implementation of a Quizizz-assisted Problem-Based Learning (PBL) model. The research employed a quasi-experimental method with a quantitative approach and a Non-Equivalent Control Group Design. The sampling technique used was purposive sampling, with the research sample consisting of two Grade 10 classes at a private senior high school in Bandung, each comprising 31 students as the experimental and control groups. The instrument used was an essay test of mathematical communication skills administered before and after the treatment. The results showed that the average N-Gain for the experimental class was 0.68 and for the control class was 0.61, both falling into the moderate category. The t-test indicated a significant difference between the two groups (p < 0.05). These findings suggest that the Quizizz-assisted PBL model is more effective than conventional instruction in improving students’ mathematical communication skills. This model also enhances students’ motivation and participation through Quizizz’s interactive features.